KINESICS INTERACTION: TOWARDS EYE CONTACT, POSTURE AND FACIAL EXPRESSION OF EDWARD AND BELLA IN A MOVIE ENTITLED “TWILIGHT” - Yekti Made Chintya Maha (Lingua Scientia, 2017)
This study discusses the nonverbal communication particularly body language. This study focuses on kinesics  such as: eye contact, posture, and facial expression of the male main character (Edward Cullen) and the female main character (Bella Swan) in Twilight movie by Stephenie Meyer. The aims of this study is to know the meaning behind those nonverbal communications of male main character and female main character as their acting in the movie. The method used to answer the problem of this study is Descriptive qualitative. The data of this study is a film entitled Twilight produced in 2008. The data is described in the form of images and words. From this study, it can be seen that there are three kinds of nonverbal communication used by the male and female main character. Those are eye contact, posture, and facial expression where the nonverbal communication used by the male character is concerned, serious, brave, romantic, cool postures, friendly and bright eyes. Whereas the female character uses dim eye contact, glace and shock posture, and amazed facial expression. It is found that there are several differences of using nonverbal communication between male and female character in the movie.